Increased Calcium-Sensing Receptor Immunoreactivity in the Hippocampus of a Triple Transgenic Mouse Model of Alzheimer's Disease - Gardenal, Emanuela; Chiarini, Anna; Armato, Ubaldo; Dal Prà, Ilaria; Verkhratsky, Alexei; Rodríguez, José J. (Frontiers in Neuroscience, 2017)
The Calcium-Sensing Receptor (CaSR) is a G-protein coupled, 7-transmembrane domain receptor ubiquitously expressed throughout the body, brain including. The role of CaSR in the CNS is not well understood; its expression is increasing during development, which has been implicated in memory formation and consolidation, and CaSR localization in nerve terminals has been related to synaptic plasticity and neurotransmission. There is an emerging evidence of CaSR involvement in neurodegenerative disorders and Alzheimer’s disease (AD) in particular, where the over-production of β-amyloid peptides was reported to activate CaSR. In the present study, we performed CaSR immunohistochemical and densitometry analysis in the triple transgenic mouse model of AD (3xTg-AD). We found an increase in the expression of CaSR in hippocampal CA1 area and in dentate gyrus in the 3xTg-AD mice when compared to non-transgenic control animals. This increase was significant at 9 months of age and further increased at 12 and 18 months of age. This increase paralleled the accumulation of β-amyloid plaques with age. Increased expression of CaSR favours β-amyloidogenic pathway following direct interactions between β-amyloid and CaSR and hence may contribute to the pathological evolution of the AD. In the framework of this paradigm CaSR may represent a novel therapeutic target.